Very fancy ζ ( n ) \zeta(n) sum

If the prime factorization of n n is n = p 1 k 1 p 2 k 2 . . . p i k i , n = p_1^{k_1}p_2^{k_2}...p_i^{k_i} , \, \, Let χ ( n ) = j = 1 i H k j \displaystyle \chi(n) = \sum_{j =1}^i H_{k_j}

Then, consider the sum:

n 2 χ ( n ) n 4 \sum_{n \geq 2} \frac{{\chi(n)}}{n^4}

The sum above can be expressed as π a ln ( π c d b ) \displaystyle \pi^a\ln \! \left( \! \sqrt[\small b]{\frac{\pi^c}{d}}\right) , where a , b , c a, b, c and d d are positive integers. Answer the smallest possible value of a + b + c + d a+b+c+d

Notation: H n H_n denotes the n th n^{\text{th}} harmonic number


The answer is 188.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Aug 14, 2019

A slightly different proof. For any prime p p and real s > 0 s > 0 define G p , s ( t ) = k = 0 e t H k p k s t 0 G_{p,s}(t) \; = \; \sum_{k=0}^\infty \frac{e^{-tH_k}}{p^{ks}} \hspace{2cm} t \ge 0 (recall that H 0 = 0 H_0=0 ). Then G p , s G_{p,s} is differentiable, and G p , s ( 0 ) = k = 0 p k s = ( 1 p s ) 1 G p , s ( 0 ) = k = 0 H k p k s = k = 1 j = 1 k 1 j p k s = j = 1 1 j p j s k = j 1 p ( k j ) s = j = 1 1 j p ( j 1 ) s ( 1 p s ) 1 = ( 1 p s ) 1 ln ( 1 p s ) \begin{aligned} G_{p,s}(0) & = \; \sum_{k=0}^\infty p^{-ks} \; = \; \big(1 - p^{-s}\big)^{-1} \\ G_{p,s}'(0) & = \; -\sum_{k=0}^\infty \frac{H_k}{p^{ks}} \; = \; -\sum_{k=1}^\infty \sum_{j=1}^k \frac{1}{jp^{ks}} \; = \; -\sum_{j=1}^\infty \frac{1}{jp^{js}} \sum_{k=j}^\infty \frac{1}{p^{(k-j)s}} \\ & = \; -\sum_{j=1}^\infty \frac{1}{jp^{(j-1)s}}\big(1 - p^{-s}\big)^{-1} \; = \; \big(1 - p^{-s}\big)^{-1}\ln\big(1 - p^{-s}\big) \end{aligned} and hence G p , s ( 0 ) G p , s ( 0 ) = ln ( 1 p s ) \frac{G_{p,s}'(0)}{G_{p,s}(0)} \; = \; \ln\big(1 - p^{-s}\big) Now χ \chi is additive, and hence X t ( n ) = e t χ ( n ) X_t(n) = e^{-t\chi(n)} is multiplicative. Thus, if we define F s ( t ) = n = 1 X t ( n ) n s t 0 F_s(t) \; = \; \sum_{n=1}^\infty \frac{X_t(n)}{n^s} \hspace{2cm} t \ge 0 then F s ( t ) = p ( k = 0 X t ( p k ) p k s ) = p G p , s ( t ) F_s(t) \; = \; \prod_p\left(\sum_{k=0}^\infty \frac{X_t(p^k)}{p^{ks}}\right) \; = \; \prod_p G_{p,s}(t) so that F s ( 0 ) = p G p , s ( 0 ) = p ( 1 p s ) 1 = ζ ( s ) F s ( t ) F s ( t ) = p G p , s ( t ) G p , s ( t ) F s ( 0 ) F s ( 0 ) = p G p , s ( 0 ) G p , s ( 0 ) = p ln ( 1 p s ) = ln ( p ( 1 p s ) ) = ln ζ ( s ) \begin{aligned} F_s(0) & = \; \prod_pG_{p,s}(0) \; = \; \prod_p\big(1 - p^{-s}\big)^{-1} \; = \; \zeta(s) \\ \frac{F_s'(t)}{F_s(t)} & = \; \sum_p \frac{G_{p,s}'(t)}{G_{p,s}(t)} \\ \frac{F_s'(0)}{F_s(0)} & = \; \sum_p \frac{G_{p,s}'(0)}{G_{p,s}(0)} \; = \; \sum_p \ln\big(1 - p^{-s}\big) \; = \; \ln\left(\prod_p\big(1 - p^{-s}\big)\right) \; = \; -\ln \zeta(s) \end{aligned} and hence F s ( 0 ) = ζ ( s ) ln ζ ( s ) F_s'(0) = -\zeta(s)\ln\zeta(s) .But this implies that n = 1 χ ( n ) n s = ζ ( s ) ln ζ ( s ) s > 0 \sum_{n=1}^\infty \frac{\chi(n)}{n^s} \; = \; \zeta(s)\ln\zeta(s) \hspace{2cm} s > 0 In the case n = 4 n=4 we obtain the sum 1 90 π 4 ln ( 1 90 π 4 ) = π 4 ln ( π 4 90 90 ) \tfrac{1}{90}\pi^4 \ln\big(\tfrac{1}{90}\pi^4\big) \; = \; \pi^4 \ln\left(\sqrt[90]{\frac{\pi^4}{90}}\right) making the answer 4 + 90 + 4 + 90 = 188 4+90+4+90=\boxed{188} .

Julian Poon
Aug 23, 2019

χ ( n ) = j = 1 i H k j = d n Λ ( d ) log d = Λ ( n ) log n 1 n = 2 χ ( n ) n 4 = n = 1 1 n 4 n = 2 Λ ( n ) log n 1 n 4 = ζ ( 4 ) log ζ ( 4 ) = π 4 90 log ( π 4 90 ) \large \displaystyle \chi(n) = \sum_{j =1}^i H_{k_j} = \sum_{d|n}\frac{\Lambda(d)}{\log d} = \frac{\Lambda(n)}{\log n} * 1 \\\\ \large \displaystyle \sum_{n=2}^{\infty} \frac{\chi(n)}{n^4} = \sum_{n=1}^{\infty}\frac{1}{n^4} \sum_{n=2}^{\infty} \frac{\Lambda(n)}{\log n} \frac{1}{n^4} = \zeta(4)\log \zeta(4) = \frac{\pi^4}{90} \log \left( \frac{\pi^4}{90} \right)

Pedro Cardoso
Aug 13, 2019

Note: See first comment and it's reply for some visual help and more details.

From the definition, we can see χ ( n ) \chi(n) is additive . This means we can group the multiples of each prime and break the sum into:

p prime i 1 χ ( p k ) ( p i ) 4 \displaystyle \sum_{p \text{ prime}} \sum_{i \geq 1} \frac{\chi(p^k)}{(pi)^4}

Where k k is the exponent of p p in the prime factorization of p i pi . Also, χ ( p k ) = H k \chi(p^k)=H_k , which allows us to break this sum even further into:

p prime k 1 j 1 1 k ( p k j ) 4 \displaystyle \sum_{p \text{ prime}} \sum_{k \geq 1} \sum_{j \geq 1} \frac{1}{k(p^{k}j)^4}

p prime k 1 1 k p 4 k j 1 1 j 4 = ζ ( 4 ) p prime k 1 1 k p 4 k \displaystyle \sum_{p \text{ prime}} \sum_{k \geq 1} \frac{1}{kp^{4k}} \sum_{j \geq 1} \frac{1}{j^4} = \zeta(4) \sum_{p \text{ prime}} \sum_{k \geq 1} \frac{1}{kp^{4k}}

From the taylor expansion of ln ( 1 x ) \ln(1-x) we get:

ζ ( 4 ) p prime ln ( 1 1 p 4 ) = ζ ( 4 ) ln ( p prime ( 1 1 p 4 ) ) - \zeta(4) \! \! \! \sum_{p \text{ prime}} \! \! \ln \! \left( \! 1 - \frac{1}{p^4} \! \right) \! \! = \! \! - \zeta(4) \ln \! \left( \! \prod_{p \text{ prime}} \! \! \left( 1 - \frac{1}{p^4} \! \right) \! \! \right) ζ ( 4 ) ln ( 1 ζ ( 4 ) ) = ζ ( 4 ) ln ( ζ ( 4 ) ) - \zeta(4) \ln \! \left( \frac{1}{\zeta(4)} \! \right) = \zeta(4) \ln \! \left( \zeta(4) \right)

Which gives us:

π 4 90 ln ( π 4 90 ) = π 4 ln ( π 4 90 90 ) \displaystyle \frac{\pi^4}{90}\ln\left( \frac{\pi^4}{90}\right) = \pi^4\ln \! \left( \! \sqrt[ \small 90]{\frac{\pi^4}{90}}\right)

And the sum is 90 + 90 + 4 + 4 = 188 90+90+4+4 = \boxed{188}

Bonus: In general n 2 χ ( n ) n s = ζ ( s ) ln ( ζ ( s ) ) \displaystyle \sum_{n \geq 2} \frac{{\chi(n)}}{n^s} = \zeta(s)\ln(\zeta(s))

The first and second expressions might be tricky to visualize just reading, so here are their first terms:

p prime i 1 χ ( p k ) ( p i ) 4 = ( 1 2 4 + ( 1 + 1 2 ) 4 4 + 1 6 4 + ( 1 + 1 2 + 1 3 ) 8 4 + . . . ) + ( 1 3 4 + 1 6 4 + ( 1 + 1 2 ) 9 4 + 1 1 2 4 + . . . ) + . . . \displaystyle \sum_{p \text{ prime}} \sum_{i \geq 1} \frac{\chi(p^k)}{(pi)^4} = \left(\frac{1}{2^4}+\frac{\left(1+\frac{1}{2}\right)}{4^4}+\frac{1}{6^4}+\frac{\left(1+\frac{1}{2}+\frac{1}{3}\right)}{8^4}+...\right)+\left(\frac{1}{3^4}+\frac{1}{6^4}+\frac{\left(1+\frac{1}{2}\right)}{9^4}+\frac{1}{12^4}+...\right)+...

p prime k 1 j 1 1 k ( p k j ) 4 = ( ( 1 2 4 + 1 4 4 + 1 6 4 + . . . ) + 1 2 ( 1 4 4 + 1 8 4 + . . . ) + 1 3 ( 1 8 4 + 1 1 6 4 + . . . ) . . . ) + ( ( 1 3 4 + 1 6 4 + . . . ) + 1 2 ( 1 9 4 + 1 1 8 4 + . . . ) + . . . ) + . . . \displaystyle \sum_{p \text{ prime}} \sum_{k \geq 1} \sum_{j \geq 1} \frac{1}{k(p^{k}j)^4} = \left(\left(\frac{1}{2^4}+\frac{1}{4^4}+\frac{1}{6^4}+...\right)+\frac{1}{2}\left(\frac{1}{4^4}+\frac{1}{8^4}+...\right)+\frac{1}{3}\left(\frac{1}{8^4}+\frac{1}{16^4}+...\right)...\right)+\left(\left(\frac{1}{3^4}+\frac{1}{6^4}+...\right)+\frac{1}{2}\left(\frac{1}{9^4}+\frac{1}{18^4}+...\right)+...\right)+...

Pedro Cardoso - 1 year, 10 months ago

Log in to reply

Also, here is some code to calculate the answer:

it prints 0.08562245363575273 0.08562245363575273 and π 4 ln ( π 4 90 90 ) 0.0856224536367 \displaystyle \pi^4\ln \! \left( \! \sqrt[ \small 90]{\frac{\pi^4}{90}}\right) \approx 0.0856224536367

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
def harmonic(n):
    harm = 0
    for i in range(1, n+1):
        harm += 1/i
    return harm


def factorization(n):
    i = 2
    factors = []
    while i * i <= n:
        if n % i:
            i += 1
        else:
            n //= i
            factors.append(i)
    if n > 1:
        factors.append(n)
    return factors


def exponents(n):
    factors = factorization(n)
    factors.append(0)
    exps = []
    count = 1
    for i in range(1, len(factors)):
        if factors[i] == factors[i - 1]:
            count += 1
        else:
            exps.append(count)
            count = 1
    return exps


def chi(n):
    c = 0
    for i in exponents(n):
        c += harmonic(i)
    return c


s = 0
for j in range(2, 10000):
    s += chi(j)/j**4
print(s)

Pedro Cardoso - 1 year, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...